Perioperative Management of Patients Receiving Antithrombotic Therapy in Schemes and Algorithms - O. N. Dzhioeva; E. A. Rogozhkina; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
Currently, antithrombotic therapy is the basis of the pathogenetic treatment of many cardiovascular diseases, such as coronary heart disease, stroke, peripheral vascular disease, as well as mechanical heart valves, heart rhythm disturbances, venous thromboembolism. At the same time, chronic use of antiplatelet and/or anticoagulant drugs is a complicating factor in invasive and surgical procedures, as it increases the risk of bleeding. In this regard, a fundamentally important and complex question arises: how to minimize the risk of periprocedural bleeding without exposing the patient to an increased risk of ischemic and thromboembolic complications? Perioperative management of patients who take antithrombotic drugs for a long time is a complex problem that depends on many factors - the risk of surgery, anesthesia, cardiovascular risks, and the urgency of surgery. Each clinical situation should be assessed individually, collegially, with the participation of surgeons, anesthesiologists, and therapists. The introduction of a checklist into clinical practice for each planned surgical patient will allow us to calculate the individual risk of bleeding and thromboembolic complications, and provide an optimal preventive strategy for perioperative management of the patient. The algorithms and schemes presented in the article for the perioperative management of patients with non-cardiac interventions are aimed at standardizing the management of patients before non-cardiac surgical interventions, which will reduce hemorrhagic risks in the presence of the necessary antithrombotic therapy.